Effects of CO2 concentration on the growth and nutrient uptake of tomato seedlings - YU Cheng-yan; DU Shao-ting; XING Cheng-hua; LIN Xian-yong; ZHANG Yong-song (浙江大学学报. 农业与生命科学版)
Hydroponic experiment was carried out to study the effects of CO2 concentration on the growth and nutrient uptake of tomato seedlings. The results showed that CO2 enrichment significantly increased the accumulation of dry matter of tomato seedlings, especially root growth which resulted in an increase of root/shoot ratio. Total uptake of N, P and K was enhanced by the developed root-system although the contents of N, P and K showed different changes. N content of tomato plant was not affected by CO2 concentration and the K content was decreased by CO2 enrichment but the P content was significantly increased in the high concentration treatment of CO2. Enrichment of CO2 largely decreased nitrate content in tomato plant, especially in the leaves. Therefore, enrichment of CO2 could not only significantly increase crop yield, but also improve the quality of farm products.